Ethionamide Alters Thyroid Receptor Gene Expression in Rats' Muscle - Ronny Lesmana; Setiawan Setiawan; Ferdyan Efza; Yuni Susanti Pratiwi; Gilang Muhamad Nur Iqbal; Hanna Goenawan; Nova Sylviana; Unang Supratman (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Ethionamide usage as one of the drug regimens still becomes a challenge due to high numbers of patients developing hypothyroid. Ethionamide had been associated with the inhibition of thyroid hormone (TH) synthesis and interestingly, ethionamide (C8H10N2S)-induced hypothyroidism is supported by its similar structure with thioamides, propythiouracil (C7H8N2S). However, hypothyroidism is not solely caused by its production, it could be caused by signaling alteration. Therefore, knowing that important TH action is determined via genomic pathway, alteration of this receptor could bring serious clinical problem. Unfortunately, there is limited study about the regulation of ethionamide and its connection on TH genomic signaling especially thyroid hormone receptor (TR) gene expression in soleus, gastrocnemius and cardiac muscle.METHODS: Thirty-eight rats were divided into control, ethionamide and propylthiouracyl groups. After 12-week treatment, rat were sacrificed, then gastrocnemius, soleus and cardiac muscles were dissected out, snap freezed using liquid nitrogen, and stored in -80oC until use. RNA was extracted and run for reverse transcription polymerase chain reaction (RT-PCR).RESULTS: In soleus muscle, ethionamide stimulated TR mRNA expressions and deiodinase compared to control group. In contrast, TRα1 gene expression was not affected by ethionamide administration. In gastrocnemius muscle, only TRβ1 gene and Dio2 gene expressions that were significantly increased compared to control group. In cardiac muscle, ethionamide significantly stimulated all the thyroid hormone receptor isoform and iodothyronine deiodinase gene expression compared to the control group.CONCLUSION: Long ethionamide treatment upregulates TR gene expressions and deiodinase in soleus and cardiac muscle, there is different expression pattern of soleus, gastrocnemius and cardiac muscle after ethionamide stimulation.KEYWORDS: ethionamide, hypothyroid, TRα1, TRα2, TRβ1, TRβ2